Global mapping and environmental drivers of epipelagic bacterial communities in the open oceans - Vitanza, Luca; Coccia, Anna Maria; Peluso, Alessia; Brandtner, David; Muratore, Anna; Ferrara, Fulvio; Lucentini, Luca; Piccioli, Andrea; La Rosa, Giuseppina; Briancesco, Rossella; , The sea care team (Frontiers in Marine Science, 2025)
IntroductionThis study provides a comprehensive analysis of the microbial communities in marine environments across different geographical regions, including the Mediterranean Sea (Northwest and Southwest), the Atlantic Ocean, the Arctic Ocean, and the Indian Ocean. The goal of this research is to examine the diversity and composition of microbial life in these ecosystems and investigate the impact of environmental factors on microbial communities.Materials and methodsHigh-throughput NGS sequencing techniques of the V3-V4 variable region of the 16S rRNA gene was employed to identify bacterial composition of the epipelagic communities in 45 water samples, using the MiSeq rRNA amplicon sequencing protocol (Illumina). Shannon index was used to described population diversity in samples.ResultsWe identified significant differences in the bacterial composition of these ecosystems, highlighting the dominance of Proteobacteria, Cyanobacteria, and specific genera such as SAR11, Alteromonas, and Synechococcus. Variations in microbial communities were strongly influenced by environmental factors such as temperature and salinity. Notably, the Mediterranean exhibited the highest microbial diversity, while the Atlantic displayed thelowest.DiscussionOur results reveal the complex interplay between microbial life and environmental conditions, emphasizing the need for long-term monitoring of these communities. These baseline data are essential for understanding the impacts of climate change and anthropogenic pollution on marine ecosystems. By improving our understanding of microbial biodiversity and its connection to ecological and human health, this study contributes to the broader goal of planetary health, offering a foundation for future efforts to mitigate the effects of environmental alterations.